2015
DOI: 10.1016/j.jpeds.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Parental Concerns, Provider Response, and Timeliness of Autism Spectrum Disorder Diagnosis

Abstract: Objective To assess age differences between first parental concern and first parental discussion of concerns with a health care provider, among children with autism spectrum disorder (ASD) versus intellectual disability/developmental delay (ID/DD), and to assess whether provider response to parental concerns is associated with delays in ASD diagnosis. Study design Using nationally-representative data from the 2011 Survey of Pathways to Diagnosis and Treatment, we compared child age at parent’s first developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
139
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 43 publications
4
139
2
2
Order By: Relevance
“…Previous research has indicated most parents delay only a few months before talking to providers about developmental concerns; however, substantial delays occur after initial provider conversations (10). This study adds to the literature by suggesting ASD diagnostic delays are also associated with long-term treatment differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has indicated most parents delay only a few months before talking to providers about developmental concerns; however, substantial delays occur after initial provider conversations (10). This study adds to the literature by suggesting ASD diagnostic delays are also associated with long-term treatment differences.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some PCPs give false reassurance (9) or fail to direct families to diagnostic resources when valid parental concerns exist (10, 11). Although major pediatric organizations recommend routine ASD screening (12, 13), only around half of PCPs screen for ASD (1416).…”
Section: Introductionmentioning
confidence: 99%
“…However, research suggests that some pediatricians were more likely to respond passively to parental concerns when children had ASD compared with an intellectual or developmental disability, suggesting that the child might “grow out of it” or expressing that it was “too early” to indicate the need for a formal assessment. 23 These passive responses were associated with increases in diagnostic delays, while more proactive responses were associated with a decrease in diagnostic delays. 23 …”
Section: The Diagnostic Odyssey Of Autism Spectrum Disordermentioning
confidence: 96%
“…23 These passive responses were associated with increases in diagnostic delays, while more proactive responses were associated with a decrease in diagnostic delays. 23 …”
Section: The Diagnostic Odyssey Of Autism Spectrum Disordermentioning
confidence: 96%
“…Screening rarely leads directly to treatment. It leads to a referral for a specialized evaluation, often with a wait of a year or more (Zuckerman et al, 2015). Once the diagnosis is confirmed, families then may have to wait again until treatment is initiated.…”
mentioning
confidence: 99%